DIGITAL LEARNING INNOVATION BASED ON ISLAMIC VALUES FOR DEVELOPING SOCIAL STUDIES EDUCATION PRE-SERVICE TEACHER COMPETENCE: A CONCEPTUAL STUDY - Pathet Diva Anis Nur Fadila; Siti Zazak Soraya (Institut Agama Islam Negeri Ponorogo, 2026)
ABSTRACT The rapid growth of digital technology has significantly impacted upon education and it also transformed the learning habits of pre-service teachers studying social studies. education Islamic learning on the other side emphasizes to integrate religious, moral and humanistic ethical values in teaching learning process. This research investigates how digital learning innovations can be used to integrate Islamic teachings into the pedagogical, professional, social and personal competencies of future social study education teachers. The study employed library research with conceptional design where different source of literature obtained from research articles and previous studies on digital learning and Islamic based education. Data analysis was used content analysis. The findings indicate that the incorporation of Islamic values in digital learning not only improves pre-service teachers’ pedagogical and technological skills, but also strengthens their spiritual identity and professional ethics. This study gives attention to the importance of value-laden digital learning in order to have well-prepared and ethical social studies education teachers prepared for an ever-changing digital world.